Esthesioneuroblastomas with intracranial extension: proliferative potential and management Estesioneuroblastomas com extensão intracraniana: análise do potencial proliferative e conduta - Marcos Tatagiba; Madjid Samii; Eva Dankoweit-Timpe; Paulo Henrique P. Aguiar; Lutz Osterwald; Ramesh Babu; Helmut Ostertag (Arquivos de Neuro-Psiquiatria)
A total of 15 patients with esthesioneuroblastomas were treated between 1978 and 1992 at the Neurosurgery Department, Nordstadt Hospital, Hannover. In 9 cases, the tumors invaded the anterior cranial fossa. One patient died before any surgical intervention. Eight tumors were operated by a combined paranasal and subfrontal approach. Gross total tumor removal was achieved in all cases. Apart from anosmia, the only postoperative complication was transient mental changes in one case. Immunohistochemical analyses with MIB 1 monoclonal antibodies, directed against recombinant parts of Ki-67 antigen, were performed to estimate the proliferative potential of the esthesioneuroblastomas. Most of the tumors showed high proliferating cell indexes, which ranged from 3 to 42% (mean, 16%). The proliferating cell index with MIB 1 showed a correlation with postoperative outcome, although this was not statistically significant. Esthesioneuroblastomas can be totally removed surgically. The proliferating cell index may reflect histologically the biological behavior of tumor. Long-term follow-up is mandatory, and imunohistochemical studies may be of help in predicting outcome. O índice proliferative celular tumoral de 8 casos cirúrgicos de estesioneuroblastomas com extensão intracraniana (9 com extensão intracraniana em um total de 15, coletados de 1978 a 1992 no Hospital Nordstadt de Hannover, Alemanha) foi avaliado através do anticorpo monoclonal MIB-1, notando -se uma correlação prognostica. A maioria dos tumores revelou índice proliferative) alto (3% a 42%, média de 16%) e a classificação histopatológica de Hyam foi utilizada. A ressecção foi radical em 100% dos casos e o acesso cirúrgico combinado (paranasal e subfrontal) o preconizado. Os autores apresentam revisão da literatura discutindo a sua casuística.